Effect of adding marjoram and rosemary leaves powder to the diet of Japanese quail males on their meat quality - Mohammed Hamad Saleh (Journal of Kerbala for Agricultural Sciences, 2026)
The present study Was conducted in the quail field of the Agricultural Research Center - College of Agriculture - University of Basra to determine the effect of adding marjoram leaves and rosemary powder to the diets of Japanese male Breedat different ages of 70, 100 and 130 days. This study includes 10 treatments: T1 means basal feed without any addition (control), T2 means adding 5g of marjoram leaf powder per 1kg of feed from 1 day old until 21 days old, T3 means adding 5g of marjoram leaf powder per 1kg of feed from 22 days old until 42 days old, T4 means adding 5g of rosemary leaf powder per 1kg of feed from 1 day old until 21 days old, T5 means adding 5g of rosemary leaf powder from 22 days old until 42 days old, T6 means adding 2.5g of each of marjoram and rosemary leaf powder in 1kg of feed from 1 day old until 21 days old, T7 means adding 2.5g of each of marjoram and rosemary leaf powder in 1kg of feed from 21 days old until 42 days old, T8 means adding 5g of marjoram and rosemary leaf powder at a concentration of 1g from 1 day old One until the end of the experiment, T9 means adding 5 g of rosemary leaf powder per 1 kg of feed from one day old until the end of the experiment, and T10 means adding 2.5 g of each of marjoram and rosemary leaf powder to 1 kg of feed from one day old until the end of the experiment. Some qualitative and sensory tests were conducted on meat samples, and the study indicators showed a significant decrease (p≤0.05) in the percentage of loss during the cooking process when adding marjoram and rosemary leaf powder and their mixture compared to the control treatment, and an improvement in sensory attributes including (color, flavor, tenderness, juiciness, and overall acceptability) through raising the sensory evaluation scores of the judges compared to the control treatment.